1963
DOI: 10.1017/s0021859600005918
|View full text |Cite
|
Sign up to set email alerts
|

Pasture type in relation to live-weight gain, carcass composition, iodine nutrition and some rumen characteristics of sheep I. Live-weight growth of the sheep

Abstract: 1. Two trials are described in which the live weights of sheep grazing four different pastures were compared. The four pastures comprised perennial rye-grass (P), perennial rye-grass plus white clover (P + C), short-rotation rye-grass (S), short-rotation rye-grass plus white clover (S + C).2. Large and highly significant differences existed between the mean live weight of the sheep on the various pastures in each trial. Thus the P sheep had a mean live weight of 107 and 102 lb. in trials I and II, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1963
1963
1986
1986

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 1 publication
0
19
0
Order By: Relevance
“…The consistently higher liveweight gains of sheep grazing pastures dominant in white clover, and to a lesser extent mixed ryegrass-white clover, than of those grazing ryegrass pastures has been demonstrated before (Rae, Brougham, Glenday, and Butler 1963;Hight and Sinclair 1965;Wilson 1966;Gallagher, Watkin, and Grimes 1966). The magnitude of the beneficial effect of white clover on liveweight gains in mixed autumn pastures appears to be influenced by herbage length, being greater with short than longer pastures.…”
Section: Autumn Growth Of Hoggetsmentioning
confidence: 92%
“…The consistently higher liveweight gains of sheep grazing pastures dominant in white clover, and to a lesser extent mixed ryegrass-white clover, than of those grazing ryegrass pastures has been demonstrated before (Rae, Brougham, Glenday, and Butler 1963;Hight and Sinclair 1965;Wilson 1966;Gallagher, Watkin, and Grimes 1966). The magnitude of the beneficial effect of white clover on liveweight gains in mixed autumn pastures appears to be influenced by herbage length, being greater with short than longer pastures.…”
Section: Autumn Growth Of Hoggetsmentioning
confidence: 92%
“…In addition. mixed swards of white clover and ryegrasses are of higher quality than the ryegrasses alone (Rae et al 1963;Rae et ai. 1964; Hight and Sinclair 1965;Grimes et ai.…”
Section: Introductionmentioning
confidence: 99%
“…White clover (Trifolium repens; C ) differs chemically in most respects from G and in particular has a higher protein and a lower cell wall content. Several studies have indicated that the productive potential of C is higher than that of grass of equivalent digestibility for both growth (Rae et al 1963;Thomson, 1979) and lactation (Rogers et al 1979;Gibb & Treacher, 1983;Thomson et al 1985).…”
mentioning
confidence: 99%